Computer aided cooling curve analysis (CACCA) of ADC-12 alloy. (2021) - V. Anil, Athul; Vijayan, Vijeesh; Sachin, B.; Rai, Prithvi Kumar; Rao, Muralidhara
Abstract: Computer aided cooling curve analysis (CACCA) is used for the determination of different characteristics of metals/alloy during solidification process. The recorded temperature data and the alloy characteristics such as solid fraction and latent heat of fusion derived using CACCA, provides an in-depth understanding of the alloy's solidification process and these information can be used as an input to casting simulation processes. Newtonian analysis a mathematical technique commonly used to determine the fraction of solid during solidification and also to fit DBL to the first derivative curve. However, few researchers have further extended this technique to determine diffusivity and enthalpy of the alloys. In this context, the presented paper explores the procedures (both experimental and theoretical) of Newtonian analysis to determine the specific heat of the alloy and also to report the solidification characteristics of ADC 12 alloy. The CACCA indicates that the nucleation of ADC 12 alloy solidifying at a rate of 0.4 °C/s will start at 574 °C with an undercooling of 46 °C and grow at 577 °C with a recalescence of 3 °C. On the other hand, the specific heat of ADC12 alloy obtained using Newtonian analysis varied between 1025 and 1275 J/Kg-K for temperature range of 600–400 °C respectively.